PERLINDUNGAN HUKUM BAGI PIHAK KREDITUR ATAS PERKARA KEPAILITAN - Ika Yanuar Margiyanti (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Bankruptcy is a situation where a debtor is unable to pay off his debts. Filing for bankruptcy can only be done if two important conditions are met, namely that a debtor has two or more creditors and the debt the debtor has is due but the debtor does not have the ability to pay the debt he has incurred. After filing for bankruptcy with the commercial court, after the bankruptcy decision is handed down, all of the debtor's assets included in the bankruptcy estate will be subject to general confiscation and later the assets will be managed and administered by a Kurator appointed by the supervised commercial court. by a supervising judge.